Household survey and bioeconomy data of rice producers in Ecuador - Labarta, Ricardo Antonio; Andrade Lopez, Robert; Castro Alvarez, Marcelo; Perez Yanez, Paulina; Marin, Diego; Urioste Daza, Sergio Alejandro; Lopera, Diana Carlina; Zuniga-Gonzalez, Carlos Alberto; Esponda Bernal, Maria Del Mar (2024)
The data was recollected by CIAT Group and Ministerio de Agricultura y Ganaderia MAG de Ecuador. This Data was facilited for the article Rice (Oryza Sativa L.) Bioeconomy: A DEA approach (VRS, CRS & Bootstrapping). The present dataset contains the original data from 612 rice farms in the five provinces of Ecuador. The dataset includes adjusted data for application in R for statistical analysis and the DEA methodology with BCC and CCR models adjusted with Bootstrap. Data were collected from 612 rice-producing farms in Ecuador during the 2019-2020 year or cycle. Details were gathered on Total Income [ti], Total Cost [tc], Total CO2 Emissions (kg CO2 eq/cycle) [te], Urea Used (kg/ha) [u], Farmer Age [age], Years of Study [Study_year], Years of Experience [experience], Land Area (ha) [area_ha], and Yield in Tons per Hectare [rend_ton_ha]. The provinces in Ecuador where the data were collected are: Guayas, El Oro, Manabi, Loja, and Los Rios.